Epstein–Barr Virus+ B Cells in Breast Cancer Immune Response: A Case Report - Aran, Andrea; Peg, Vicente; Rabanal, Rosa Maria; Bernadó, Cristina; Zamora, Esther; Molina, Elisa; Arribas, Yago A.; Arribas, Joaquín; Pérez, José; Roura-Mir, Carme; Carrascal, Montserrat; Cortés, Javier; et al. (Frontiers in Immunology, 2021)
EBV-specific T cells have been recently described to be involved in fatal encephalitis and myocarditis in cancer patients after immune checkpoint therapies. Here we report the study of a human triple negative breast cancer tumor (TNBC) and EBV-transformed B cells obtained from a Patient-Derived Xenograft (PDX) that progressed into a lymphocytic neoplasm named Xenograft-Associated B Cell Lymphoma (XABCL). TCR high-throughput sequencing was performed to monitor the T cell clonotypes present in the different samples. Forty-three T cell clonotypes were found infiltrating the XABCL tissue after three passes in mice along 6 months. Eighteen of these (42%) were also found in the TNBC biopsy. TCR infiltrating the XABCL tissue showed a very restricted T cell repertoire as compared with the biopsy infiltrating T cells. Consequently, T cells derived from the TNBC biopsy were expanded in the presence of the B cell line obtained from the XABCL (XABCL-LCL), after which the TCR repertoire obtained was again very restricted, i.e., only certain clonotypes were selected by the B cells. A number of these TCR had previously been reported as sequences involved in infection, cancer and/or autoimmunity. We then analyzed the immunopeptidome from the XABCL-LCL, to identify putative B cell associated peptides that might have been expanding these T cells. The HLA class I and class II-associated peptides from XABCL-LCL were then compared with published repertoires from LCL of different HLA typing. Proteins from the antigen processing and presentation pathway remained significantly enriched in the XABCL-LCL repertoire. Interestingly, some class II-presented peptides derived from cancer-related proteins. These results suggest that bystander tumor-infiltrating EBV+ B cells acting as APC may be able to interact with tumor-infiltrating T cells and influence the TCR repertoire in the tumor site.